A comparative analysis of the UN declaration, global business compact, and religious morals in determining global values for business and their application to Islamic marketing. Issue 4 (8th October 2018) - Fraedrich, John; Althawadi, Othman; Bagherzadeh, Ramin
Abstract : Purpose: The continued rise of the multinational and debate as to what constitutes global business values is predicated on the UN Declaration and Global Business Compact. This research suggests both documents explicitly exclude the existence of a foundational ethereal power creating morals thereby nullifying two thirds of the general population's belief system. The authors argue against humanism as a global value beginning and suggest theism as a better origin and use the scientific method to introduce mathematical axioms supporting theism and complimenting humanism. Ontologically, the theist becomes a stronger base for the scientific inquiry into morals, values and business ethics. A comparison of major religious morals revealed eight factors: assurance; candor, fairness and honesty; character, integrity, truthfulness and exacting in truth; charity and compassion; environment; perseverance and tolerance; sacrifice; and seriousness. The research suggests that the UN documents do not adequately reflect these morals suggesting a change for businesses especially in Islamic regions. Design/methodology/approach: A comprehensive review of religious materials emphasizing morals rather than customs, eternal entity description or negative behaviors yielded 1, 243 morals and associated synonyms via six religions (Buddhism, Confucianism, Christianity, Hinduism, Islam and Judaism) representing 4.5 billion people. All positive morals were cross-referenced and only common items across all six religions were included. With the 29 common morals, the authors completed a word meaning search and did a second comparison that yielded 8 moral factors or constructs. Findings: Eight moral factors were found to be common in all major religions (assurance, fairness/honesty, character/integrity, charity/compassion, environment, tolerance, sacrifice and seriousness). By using the scientific method (Axioms), the authors argue that theism is a better beginning to researching morals and values within business and marketing. Social implications: Multinationals should be made aware of the disconnect between the underlying problems of the Global Business Compacts' values and the global morals identified. The results suggest adopting a codification system based on the pertinent morals as related to economic theories: capitalism, socialism and theism. The use of theism as a base to business and marketing ethics includes billions of customers and employees and their belief systems that should increase the validity and reliability of actions associated with corporate social responsibility, the environment and best practices. Originality/value: The UN Declaration and subsequent Global Business Compact are argued to be flawed by its exclusion of religious morals and the historical period in which it was created. By using the scientific method and creating two axioms, the base to all business and marketing ethics must shift to the common moral factors identified.